THE EFFECT OF CROSSWORD PUZZLE THERAPY (CPT) ON THE COGNITIVE FUNCTION OF ELDERLY IN SUDAGARAN OLD AGE HOME (PPSLU), BANYUMAS - Komsin, Nabila Karimah; Isnaini, Nur (Jurnal Ilmiah Keperawatan Indonesia (JIKI), 2020)
Decreased cognitive function in the elderly will affect their daily activities and make them depend on others. The solution to overcome the problems is improving the elderly cognitive function. Crossword Puzzle Therapy (CPT) is a non-pharmacological therapy used to prevent cognitive decline. This research aimed to discover the effect of Crossword Puzzle Therapy (CPT) on the cognitive function of the elderly in an old age home located in Sudagaran, Banyumas.This was Quasy Experimental research with a Pre and Posttest with Control Group approach. There were 36 elderly taken as the research sample using a total sampling technique. The research instrument used was MMSE. Data obtained were analyzed using Mann Whitney. The results showed of majority of the respondents were women. The average age of respondents was in the range of 60-74 years. Most of them did not go to school or only graduated from primary school. MMSE scores of the elderly who got Crossword Puzzle Therapy (CPT) increased significantly compared to those who did not. Based on the Mann Whitney test result, the Asymp.Sig value was 0,000 (P value 0.05) there was an effect of Crossword Puzzle Therapy (CPT) on the cognitive function of the elderly in Sudagaran Old Age Home, Banyumas. While based on the Shapiro-Wilk test, the p value was 0.05. Keywords: Crossword Puzzle Therapy (CPT); elderly; cognitive function.